Gloeocantharellus guidongensis (Gomphaceae, Gomphales), a new species from southern China - Deng, Peng-Tao; Chen, Xiao-Xia; He, De-Cao; Li, Wen; Zhang, Ping (Phytotaxa, 2026)
Gloeocantharellus is a small genus that has rarely been reported before in China. Based on morphological and phylogenetic evidence, we describe a new species, Gloeocantharellus guidongensis, collected from southern China. Phylogenetic analysis based on nucleotide sequences of three genetic loci (ITS, LSU and ATP6) confirm that G. guidongensis is well supported within the genus Gloeocantharellus and forms a distinct lineage. Gloeocantharellus guidongensis is distinguished by a unique phylogenetic position, occurrence in southern subtropical mixed forests of China, and irregularly verrucose spores. A key to the known species of Gloeocantharellus reported from China is also provided.